The new goals of EU competition law: sustainability, labour rights, and privacy - Marios C. Iacovides; Konstantinos Stylianou (European Law Open)
Competition law is experiencing a transformation from a niche economic tool to a Swiss knife of broader industrial and social policy. Relatedly, there is a narrative that sees an expansive role for competition law in broad areas such as sustainability, privacy, and workers and labour rights, and a counternarrative that wants to deny it that role. There is rich scholarship on this area, but little empirical backing. In this article, we present the results of a comprehensive empirical research into whether new goals and objectives such as sustainability, privacy, and workers and labour rights are indeed endorsed in EU competition law and practice. We do so through an investigation into the totality of Court of Justice rulings, Commission decisions, Advocate General opinions, and public statements of the Commission. Our findings inject data into the debate and help dispel misconceptions that may arise by overly focusing on cherry-picked high-profile decisions while overlooking the rest of the EU’s institutional practice.